2017
DOI: 10.1002/pro.3128
|View full text |Cite
|
Sign up to set email alerts
|

Structural, thermodynamic, and phosphatidylinositol 3‐phosphate binding properties of Phafin2

Abstract: Phafin2 is a phosphatidylinositol 3‐phosphate (PtdIns(3)P) binding protein involved in the regulation of endosomal cargo trafficking and lysosomal induction of autophagy. Binding of Phafin2 to PtdIns(3)P is mediated by both its PH and FYVE domains. However, there are no studies on the structural basis, conformational stability, and lipid interactions of Phafin2 to better understand how this protein participates in signaling at the surface of endomembrane compartments. Here, we show that human Phafin2 is a mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 33 publications
1
11
0
Order By: Relevance
“…Both the Phafin2 PH and FYVE domains showed a preference for PtdIns3P. The FYVE domain was highly selective for this phosphoinositide, whereas the PH domain showed a less stringent binding profile and also bound weakly to PtdIns4P and PtdIns5P (Fig 3f) This is in line with previous reports 19, 21 . As we observed that the N-terminal region of Phafin2 was also required for the first Phafin2 localization phase and its deletion had the same effect as impairing the lipid-binding activity of the PH domain, we asked if this region is required to form a functional PH domain.…”
Section: Resultssupporting
confidence: 92%
“…Both the Phafin2 PH and FYVE domains showed a preference for PtdIns3P. The FYVE domain was highly selective for this phosphoinositide, whereas the PH domain showed a less stringent binding profile and also bound weakly to PtdIns4P and PtdIns5P (Fig 3f) This is in line with previous reports 19, 21 . As we observed that the N-terminal region of Phafin2 was also required for the first Phafin2 localization phase and its deletion had the same effect as impairing the lipid-binding activity of the PH domain, we asked if this region is required to form a functional PH domain.…”
Section: Resultssupporting
confidence: 92%
“…Phafin2 contains a PH and a FYVE domain, both of which are involved in lipid binding ( Fig. 1 A) ( Matsuda-Lennikov et al, 2014 ; Schink et al, 2017 preprint; Tang et al, 2017 , 2020 ). JIP4 interacts with Phafin2 only through the Phafin2 PH domain, as deletion of the PH domain – but not the FYVE domain – abolished expression of the reporter gene in a yeast two-hybrid assay ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In the present study, we show that a previously uncharacterized region of JIP4 interacts with the PH domain of the phosphoinositide-binding protein Phafin2, recruiting JIP4 to early macropinosome membranes. Phafin2 binds PtdIns3P -generated by the PtdIns 3-kinase VPS34 -through its FYVE domain, which localizes it to endosomes and macropinosomes (Pedersen et al, 2012;T.-X. Tang et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although membrane nucleation has been established as a key step in the autophagic process, the origin of the membrane that gives rise to the phagophore, and subsequently the autophagosome, remains unclear. Elongation and expansion of the phagophore membrane are key steps in the autophagic process (17). The autophagy related protein Atg12-Atg5-Atg16 and Atg8 conjugation systems, which are inter-related ubiquitin-like conjugation pathways, regulate this stage in both yeast and mammals (18).…”
Section: The Molecular Mechanism Of Autophagymentioning
confidence: 99%